I_2-Asymptotically Lacunary Statistical Equivalence of Weight g of Double Sequences of Sets - Kişi, Ömer (Sarajevo Journal of Mathematics, 2022)
In this paper, our aim is to introduce new notions, namely, Wijsman asymptotically I_2-statistical equivalence of weight g, Wijsman strongly asymptotically I_2-lacunary equivalence of weight g and Wijsman asymptotically I_2-lacunary statistical equivalence of weight g of double set sequences. We mainly investigate their relationship and also make some observations about these classes.